Crop Rotations in California Rice Systems: Assessment of Barriers and Opportunities - Rosenberg, Sara; Crump, Amanda; Brim-DeForest, Whitney; Linquist, Bruce; Espino, Luis; Al-Khatib, Kassim; Leinfelder-Miles, Michelle M.; Pittelkow, Cameron M. (Frontiers in Agronomy, 2022)
Flooded rice soils are unique in terms of maintaining soil fertility and long-term productivity, allowing continuous rice systems to contribute greatly to global food supply. Yet increasing herbicide resistant weed pressure, water scarcity, and other sustainability challenges suggest a need to explore options for cropping system diversification. However, little research has evaluated the current obstacles limiting diversification of rice systems in different contexts. During summer and fall of 2020 we interviewed 42 rice growers to i) assess the perceived benefits and challenges of crop rotation in the context of California rice systems and ii) identify the factors influencing decision-making and barriers to adoption. Rice-based cropping systems ranged from high to low diversity across three different categories of growers (conventional rotations > organic > continuous rice). Key factors influencing the feasibility of rotations were soil limitations, production costs and productivity level of alternative crops, water and equipment requirements, market access, and regional differences. Generally, growers agreed that weed control and reduced reliance on herbicides were benefits of rotation. Similarly, growers who rotated described soil health as a primary benefit that decreases the need for fertilizer and pesticide inputs. However, there were many challenges to implementing rotations including heavy clay soils with poor drainage, lack of available contracts and markets for other crops, financial barriers such as land ownership and farm infrastructure (size of operation and available labor and equipment), and limited experience and knowledge of other viable crops. In terms of economic feasibility, those who only grow rice believed that other crops are less profitable, while those who rotate said that rotations increased profitability. Our research indicates that soil conditions is an important limitation, but other economic, social, and cultural barriers also strongly influence the potential for the diversification of rice systems.